Approximating the Lateral Distribution Function of Cherenkov Radiation as a Function of the Particle Type for Tunka-133 Array - Khadhum, Zena Fadhel; Mahdi, Hassan Abdullah; Al-Rubaiee, A A (Al-Nahrain Journal of Science, 2018)
The main interest of the present work is in analysing the lateral distribution function (LDF) of Cherenkov radiation from particles that produced in Extensive Air Showers (EAS). The simulation of LDF of Cherenkov radiation is fullfiled by utilizing the CORSIKA programe at 3∙1015 eV of the primary energy around the knee region for many primaries for vertical showers for Tunka-133 array conditions. Depending on the numerical simulation results of Cherenkov light LDF, sets of parameterized polynomial functions are resetted for several particles as a function of primary particle type. The comparison between the approximated LDF of Cherenkov radiotion with the LDF which has been simulated using CORSIKA program for Tunka-133 array is verified for several primary particles for vertical EAS cascade.